Epidemiology of youth sports concussion - Jinguji, T. M.; Krabak, B. J.; Satchell, E. K. (Physical Medicine & Rehabilitation Clinics of North America, 2011)
The overall prevalence of concussion is high school sports is unknown. In general, concussions in this age range occur much more frequently in games than in practice. Also for sports in which both sexes participate, reported concussion rates are higher for female than male high school athletes. Recent data show that the time required for return to play and resolution of symptoms is similar for women and men. Very little is known about the epidemiology of concussions in middle school-aged athletes and younger children.